Balanço entre intemperismo químico e remoção do solo na bacia do Ribeirão Monjolo Grande, Ipeúna (SP), determinado por geoquímica fluvial - Spatti Júnior, Eder Paulo [UNESP] (2014)
This study aimed to evaluate the balance between chemical weathering and soil removal in the Monjolo Grande Stream basin, Ipeúna (SP), determined by river geochemistry. The results indicated a material dissolved transported of 6.33 t/km²/yr or 182.5 t/yr, due to chemical weathering processes of rocks in this watershed. In relation to sediment yield, it was obtained a flux of 31 t/km²/yr or 887 t/yr. The rates of chemical weathering and soil removal were 7 and 26 m/Ma, respectively, indicating a decrease in soil thickness in the Monjolo Grande basin under current climatic conditions. Simulation of different scenarios indicated a value of 2.65 m/Ma to rates of chemical weathering and soil removal will be equal. Furthermore, only in dry weather conditions the rates of chemical weathering will be greater than the soil removal.